Investigating Clinical and Biochemical Variances between Drug Resistant and Drug Susceptible Enteric Fever in Children - Shahina Hanif; Mohammad Hanif Memon; Farhan Saeed; Erum Saboohi; Farhat Ali; Marium Akram (Liaquat National Journal of Primary Care)
Background: Two main types of resistance are observed in Salmonella Typhi (S. Typhi): Multi-Drug Resistant (MDR) and Extensively Drug-Resistant (XDR). The treatment of MDR typhoid fever often involves oral medication and intravenous therapy. When treating XDR enteric fever, the choice of antibiotics depends on the patient’s clinical condition. Objective: To determine clinical and biochemical variances between drug-resistant and drug-susceptible enteric fever in children Methods: The cross-sectional study was conducted in the Department of Pediatrics, Sambros Hospital, Karachi, from February to August 2018, a total of 143 patients were admitted from age 6 months to 13 years. Data collection and analysis were conducted using IBM SPSS, version 25. Results: Out of the 143 patients, the majority were males (61.5%) and the mean age was 6.19±3.82 years. 15.4% had DrugSusceptible Salmonella Typhi, while 84.6% had Drug-Resistant (including MDR and XDR) S. Typhi. Duration of fever (p=0.002) and hospital stay (p=0.025) were positively associated with drug-resistant enteric fever. Significant associations with hepatomegaly, splenomegaly, and mesenteric lymphadenopathy were noted in the drug-resistant group. None of the laboratory parameters was significant between the drug-sensitive and drug-resistant groups. Conclusion: The incidence of drug-resistant enteric fever is very high with longer duration of fever and hospital stay more typhoid complications, which could have serious consequences in the future. Clinical findings including hepatomegaly, splenomegaly, and mesenteric lymphadenopathy were found to be significantly different among the two types of enteric fever whereas laboratory parameters were similar.